Physiology of exercise and healthy aging - Taylor, Albert W.; Johnson, Michel J. 1966- (Human Kinetics, 2008)
Aims to blend the science of exercise physiology with the ageing process. This book outlines the theories on ageing, the ageing, process, the structural and functional changes that characterise advancing age and the exercise programming concerns for the aged, as well as the benefits of exercise and physical activity